Stenting of the caudal aorta and aortic trifurcation for the treatment of thrombosis in 7 dogs. (7th February 2022) - Gavin, Kelly A.; Weisse, Chick; Berent, Allyson C.
Abstract: Background: Aortic and aortoiliac thrombosis in dogs causes disease and death. Objective: To describe the procedure and outcomes for stenting the caudal aorta and aortoiliac trifurcation. Animals: Seven client‐owned dogs that underwent aortic/aortoiliac stenting for treatment of thrombosis. Methods: Retrospective multi‐center investigation. Medical records were reviewed for dogs that underwent stenting of the aorta or aortoiliac trifurcation between 2008 and 2020. Information collected included history, signalment, clinicopathologic data, diagnostic imaging, procedure reports, and outcomes. Results: Seven dogs with an occlusive thrombus located at or near the aortic trifurcation were included. Four of 7 dogs were non‐ambulatory. Hind limbs were paretic in 5 dogs, paralyzed in 1 dog, and claudication alone was noted in 1 dog. Five of the 7 dogs had protein‐losing nephropathy (PLN). Of 5 dogs with PLN, 1 had protein‐losing enteropathy (PLE) and controlled hypothyroidism and 1 had caudal aortic chondrosarcoma. Two dogs had no identified underlying disease. Angiography was performed before catheter directed thrombolysis and stent placement. No deaths occurred during the procedure. Postoperative complications included pain (4/7), bruising and edema (3/7), bruising only (1/7), and edema only (1/7). Median survival time (MST) of the 7 dogs was 264 days (range, 1‐1053 days). Five of 7 dogs were ambulatory within 2 days of stenting and survived to discharge with a MST of 425 days (range, 208‐1053 days). Conclusions and Clinical Importance: Stenting of the aorta and aortoiliac trifurcation can provide an apparently safe and effective treatment with rapid return to ambulation for some dogs with aortic thrombosis.